Análisis de los costos indeterminados y su incidencia en el valor de venta en la microempresa artesanal Moder mueble del cantón Salcedo 2021 - Tonato Silva, Alex Darío (2022)
The objective of this project is to analyze the indeterminate costs and the sale value in the artisan furniture store "Moder Mueble" of the Salcedo canton in 2021, for the development of this proposal the ABC cost system was implemented, with the objective of determining a analysis of costs by production activities and their impact on profitability. The main research problem is based on the fact that the furniture store does not have a cost system to be able to identify if the prices of the products it offers are consistent with the manufacturing prices and thus be able to know if it has an acceptable profitability. The manufacturing process of the goods carried out by the company goes through four production phases, of which in each of them the costs incurred in production must be identified. A process cost system is used in manufacturing industries to determine the total costs of manufacturing a unit of product. It is particularly used in environments where creation goes through multiple processes. The methodology that was used in the research project, related to the development of production processes and their impact on profitability, emphasized a qualitative and quantitative, descriptive approach because it allowed us to know what the current situation is going through. Arriving to determine that the results obtained in the survey related to the questions used for the crossing of variables and the verification of hypotheses. Once x has been calculated, it is determined that its value is greater than critical x, which is why it is in the Ho rejection zone, so HI is accepted. Concluding that, at present, "Moder Mueble" does not have a cost model; performs its expense record through an empirical system. In conclusion, an ABC cost model will improve production management, reduce manufacturing costs.